Epidemiological analysis of injuries in soccer referees: A systematic review - Sebastián Rodríguez; Angie Natalia Suarez-Cuervo; Catalina León-Prieto; María Fernanda Rodríguez-Jaime (Elsevier, 2024)
Objective: To provide a broader epidemiological profile of injuries in male soccer referees by systematically searching for observational scientific studies. Methodology: Searches were conducted in PubMed, Web of Science and Sciencedirect, following PRISMA guidelines. Of the 12,246 studies identified, 5 were included after a selection process. They were evaluated using the STROBE checklist, complemented with the cohort checklist provided by SIGN. Results: A total of 433 head referees and 467 assistant referees were analyzed. The most prevalent injuries among the main referees after the matches were to the Achilles tendon and the ankle/foot, while for the assistants it was in the lower leg. During the physical tests, the most common injuries among the main referees affected the knee, hip and groin, and in the assistants, the hip and groin. The most frequent injuries throughout their careers were in the hip and groin for the main referees, and in the knee for the assistants. In the last twelve months, the most common injury was in the thigh for principals and again in the knee for assistants. Lower leg and Achilles tendon injuries stood out as the most incident over a 12-month period, followed by ankle/foot injuries in both groups. For a 30-day follow-up period, the most frequent injury was in the lower back for both groups. Conclusion: Injuries in soccer referees require meticulous attention, manifesting themselves at different times and in different areas of the body during physical tests, matches and throughout their careers. Registry number: CRD42024547881